Situating walkability: examining walkability elements on recurring routes - Tartia, Jani (TeMA - Journal of Land Use, Mobility and Environment, 2025)
Walking is widely regarded as a ubiquitous, affordable, healthy and zero-carbon mobility mode that enhances the liveliness and inclusivity of urban spaces. In recent years, the concept of ‘walkability’ has emerged as a central criterion for assessing the sustainability and liveability of cities. Walkability elements and metrics are often employed to map urban environments, evaluating their capacity to facilitate or hinder walking from the perspective of experts and professionals. However, how do these metrics relate to the situated subjective walker-street relations, contexts and experiences? This study employs ethnographic mobile research methods to examine the connections between walkability elements of the physical built environment and the everyday walking experiences on recurring day-to-day routes in two mid-sized cities in Finland. Utilizing walkability metrics related to visual urban design elements from research literature, the study explores the role of the elements in shaping the walking experience in the context of regularly travelled routes and the subjective body-environment relations. The study highlights that the walkability elements can act as important anchoring points in the study of the body-environment relations in the context of the habitual everyday urban mobility. The importance of ‘imageability’ and ‘complexity’ elements is discussed, as well as the role of temporality and ‘rhythm’ in the walking experience.